PENERAPAN MESIN PENGERING TIPE RAK BERBASIS TEKNOLOGI INFRARED BURNER UNTUK PENINGKATAN HASIL OLAHAN BUNGA TELANG PADA INDUSTRI RUMAH TANGGA - Rizal, Reda; Fahrudin, Fahrudin; Sembiring, Rosali Colia; Martana, Budhi (Servirisma, 2023)
The community-based empowerment carried out at home industries in Ciantra Village is a form of dedication by the Higher Education staff to community groups in producing butterfly pea-based processed products. The problems faced by partners, namely the drying process of butterfly pea flowers is still done conventionally by drying in the sun, and the drying process takes quite a long time, especially during the rainy season. Solutions that can be offered to overcome these problems with the application and assistance of infrared burner technology-based dryers. The aim of the community partnership empowerment program activities is to carry out technology transfer to home industries and to improve the quality of butterfly pea products. The stages of the activities used in the implementation of the community partnership empowerment program are socialization, application of the dryer, how to use the dryer, assistance, and evaluation. The results achieved through this program are that partners are able to understand the process of drying butterfly pea flowers, are skilled in the drying process of butterfly pea using the technological innovations that have been provided, and the availability of dryers based on infrared technology that partners can use to improve the drying results of butterfly pea flowers.